Effect of perceived autonomy supports on exercise persistence for adolescents: an integrated model based on basic psychological needs theory and the theory of planned behavior - Li, Xuening; Zhu, Jianyong; Yu, Huasen; Lin, Jiabin (Frontiers in Psychology, 2025)
IntroductionAlthough previous research has confirmed a positive association between perceived autonomy support and adolescents’ exercise persistence, the psychological mechanisms underlying this relationship remain insufficiently explored. The study aims to investigate the relationship and mechanisms linking perceived autonomy support to exercise persistence in adolescents, based on the integrated framework of basic psychological needs (BPN) and the theory of planned behavior (TPB).MethodsUsing a simplified stratified random sampling method, 4,345 adolescents aged 10–20 years completed measures of perceived autonomy support, BPN, TPB, and exercise persistence. Structural equation modeling (SEM) was constructed to test the effectiveness of the integrated model and examine hypothesized pathways.ResultsSEM analysis showed that perceived autonomy support directly predicted exercise persistence. This relationship was also partially mediated via BPN alone and by the chained mediation of BPN and TPB constructs. Furthermore, this indirect effect was moderated by educational stage and gender. For junior high school students, behavioral attitudes did not significantly influence behavioral intentions. Both behavioral intentions and perceived behavioral control positively affected exercise persistence, whereas perceived behavioral control did not significantly influence exercise persistence among female senior high school students.ConclusionThese findings confirm the applicability of integrating BPN and TPB to explain how exercise support environment foster adolescents’ exercise persistence. They further highlight the importance of tailoring interventions strategies to differences in educational stage and gender. Further research should build on this integrated model to design stage- and gender- specific interventions and examine their longitudinal effectiveness across different developmental periods.